Articulating and ameliorating elder abuse in Australia - Kingsley, Elizabeth J.S. (Curtin University, 2002)
The abuse of older people is a largely unrecognised and under acknowledged social problem in Australia. My major objective in undertaking the work, which is represented by the original published articles that comprise the thesis, was to make a scholarly and practical contribution toward the minimisation of 'elder abuse. This objective was achieved with the development and implementation of a series of studies that articulated and ameliorated elder abuse in Australia.The thesis provides an erudite synthesis of these studies, which fall into four themes that illustrate the nature and scope of my theoretical and professional work in elder abuse. Much of the work was guided by a conceptual framework of ways of knowing in nursing, and was underpinned by the principles and practice of community development and participatory community-based action processes.The outcomes of these studies include work with three stakeholder groups: professionals who deal with elder abuse, older people who are victims or potential victims of abuse, and those who perpetrate abuse on an older person. The work, illustrated in the four themes, includesthe articulation of elder abuse issues with West Australian aged care workersthe development of elder abuse protocols, policy guidelines and ethical principles, to guide professional practice in abuse prevention and interventionthe design and implementation of participative community programs to empower older people, and their carers, to resist being abused or abusing and to assist perpetrators stop their abusethe amelioration of abuse of nursing home residents by staff.The thesis situates my conceptual and clinical effort within the wider corpus of Australian knowledge and practice on elder abuse and contributes to addressing the social problem of elder abuse within the context of Australian aged care.